Footprints of global change in marine life: Inferring past environment based on DNA methylation and gene expression marks. Issue 3 (29th December 2020) - Anastasiadi, Dafni; Shao, Changwei; Chen, Songlin; Piferrer, Francesc
Abstract: Ocean global warming affects the distribution, life history and physiology of marine life. Extreme events, like marine heatwaves, are increasing in frequency and intensity. During sensitive stages of early fish development, the consequences may be long‐lasting and mediated by epigenetic mechanisms. Here, we used European sea bass as a model to study the possible long‐lasting effects of a marine heatwave during early development. We measured DNA methylation and gene expression in four tissues (brain, muscle, liver and testis) and detected differentially methylated regions (DMRs). Six genes were differentially expressed and contained DMRs three years after exposure to increased temperature, indicating direct phenotypic consequences and representing persistent changes. Interestingly, nine genes contained DMRs around the same genomic regions across tissues, therefore consisting of common footprints of developmental temperature in environmentally responsive loci. These loci are, to our knowledge, the first metastable epialleles (MEs) described in fish. MEs may serve as biomarkers to infer past life history events linked with persistent consequences. These results highlight the importance of subtle phenotypic changes mediated by epigenetics to extreme weather events during sensitive life stages. Also, to our knowledge, it is the first time the molecular effects of a marine heatwave during the lifetime of individuals are assessed. MEs could be used in surveillance programs aimed at determining the footprints of climate change on marine life. Our study paves the way for the identification of conserved MEs that respond equally to environmental perturbations across species. Conserved MEs would constitute a tool of assessment of global change effects in marine life at a large scale.